2015
DOI: 10.1177/0003489415595425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Balloon Dilation for Idiopathic Laryngotracheal Stenosis on Voice Production

Abstract: Our sample of patients with idiopathic laryngotracheal stenosis had a mild-moderate dysphonia that improved with balloon dilation. Importantly, adverse effects on voice that can occur with open procedures were not observed. Patient perception of dysphonia improved while fundamental frequency range was maintained and aerodynamic parameters remained within or moved toward the normal range. Larger prospective studies are warranted to further evaluate changes in voice production associated with balloon dilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…Idiopathic subglottic stenosis is well suited to assessment with PROMs because the primary clinical manifestation of this disease is a perceptual and psychosocial symptom with an impact on many facets of QOL . Several groups have used PROMs to show that patients with airway stenosis tend to improve along many dimensions after surgery to widen the glottis and/or subglottic airway, including along the dimensions of voice and dyspnea symptoms . Our model agrees with the inclusion of both of these dimensions, as well as including questions about cough (which can be persistent in ISGS) and general overall health.…”
Section: Discussionsupporting
confidence: 67%
“…Idiopathic subglottic stenosis is well suited to assessment with PROMs because the primary clinical manifestation of this disease is a perceptual and psychosocial symptom with an impact on many facets of QOL . Several groups have used PROMs to show that patients with airway stenosis tend to improve along many dimensions after surgery to widen the glottis and/or subglottic airway, including along the dimensions of voice and dyspnea symptoms . Our model agrees with the inclusion of both of these dimensions, as well as including questions about cough (which can be persistent in ISGS) and general overall health.…”
Section: Discussionsupporting
confidence: 67%
“…Regardless of these possible reasons for variability across studies, the results from the present investigation indicate that patients with SGS present with voice disorder severity ranging from mild to moderate based on auditory‐perceptual, aerodynamic, acoustic analyses, and patient‐reported measures. Presumably, the greater the severity of the stenosis, the more severe the voice disorder; however, this is yet to be proven because many patients seek out and receive surgical intervention in the form of balloon dilation prior to open laryngeal procedures …”
Section: Discussionmentioning
confidence: 97%
“…Smith et al also observed voice disorders in the mild‐to‐moderate range based on selected acoustic measures prior to surgical management of idiopathic SGS in a similar group of patients to those in the present study. Most recently, Hoffman, Brand, and Dailey performed a study of 10 patients with SGS who received balloon dilation as an alternative to the potentially more detrimental effects of open laryngeal surgeries such as CTR. The authors documented presurgical voice disorder severity in the very mild range based on the VHI and the severe range based on the auditory‐perceptual Grade, Roughness, Breathiness, Asthenia, Strain Scale .…”
Section: Discussionmentioning
confidence: 99%
“…Perceptual voice quality evaluation using the CAPE-V assessment did not demonstrate improvement in our sample population, a result that is consistent with those of previous perceptual voice evaluation studies. 5,6 The lack of concordance between improvement in CAPE-V and V-RQOL scores may be because the patient’s self-rated V-RQOL improvement reflects that they no longer run out of breath or that they are less anxious and/or depressed about their airflow related to voice, rather than the quality of voice grade, roughness, breathiness, asthenia, or strain that perceptual raters assess. Acoustic and aerodynamic measures evaluated largely remained unchanged, although maximum phonation time and maximal high-pitch frequency improved after the airway intervention.…”
Section: Discussionmentioning
confidence: 99%